Mini-invasive bilateral transfacet screw fixation with reconstruction of the neural arch for lumbar stenosis: A two centre case series. Issue 4 (August 2022) - Bochicchio, Michele; Aicale, Rocco; Romeo, Rocco; Nardi, Pier Vittorio; Maffulli, Nicola
Abstract: Background and purpose: Lumbar stenosis and instability frequently coexist. Spinal canal decompression is often combined with fixation of the relevant vertebral segment and can be performed using different techniques and devices, including pedicle screws and interspinous devices and facet screws. The present study evaluates the clinical outcome of laminectomy and single-level fusion using a minimally invasive technique for rigid posterior spinal column fixation with two cross-linked lag screws. Methods: The records of patients operated from 2012 to 2016 were retrieved from the computerised medical record database system. Data on age, sex, surgical level, type of deficit and disease were collected. The Oswestry Disability Index (ODI) and Short Form-36 (SF-36) questionnaires were administered pre-operatively and at 1, 6, 12 and 24 months after surgery. Main findings: A total of 46 consecutive patients were operated between January 2012 to October 2016. One intraoperative complication was reported, and 4 patients experienced radiographic pseudarthrosis postoperatively. Five patients underwent additional surgery. The lumbar and lower limb VAS score, ODI and SF-36 scores showed statistically significant improvement for each score at the first and last follow-up (p < 0.01). Conclusion: Percutaneous lumbar transfacet screw placement with the Facet-Link ® system is feasible and safe but with a relatively high rate of poor articular fusion. This technique can reduce the morbidity of single-level lumbar spinal stenosis and mild instability and improve patient outcome scores. Comparative studies, including randomised controlled trials, are needed to confirm these findings. Highlights: When lumbar spinal stenosis does not respond to conservative management, surgery is recommended, and many surgical techniques are available with the aim to decompress the lumbosacral roots at the spinal canal and foramina. We report the results of a two centre case series in patients with LSS and mild instability managed with laminectomy and one-level fixation with the Facet-Link® device trough Transfacet pedicle screw fixation. Minimally invasive transfacet screw fixation decreases surgical trauma and allows sound fixation and decompression to reliably relieve symptoms. The rate of bony fusion was relatively excellent, with only four patients evidencing radiograph pseudarthrosis, and nearly three quarters showing evidence of solid fusions. Mini-invasive lumbar transfacet screw placement with the Facet-Link® system is feasible and safe despite rate of pseudarthrosis and can be performed accurately in a predictable manner.